automaticloveletter
  • automaticloveletter
can someone help me with this
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
automaticloveletter
  • automaticloveletter
y = -4x - 19 y = 2x − 1
TheSmartOne
  • TheSmartOne
since the same y equals to something, then both equal to each other, so solve for x: -4x - 19 = 2x − 1
automaticloveletter
  • automaticloveletter
-3?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
y=-19/6 x=-19/3
TheSmartOne
  • TheSmartOne
@automaticloveletter correct, so x=-3
TheSmartOne
  • TheSmartOne
so now plug x=-3 back into any equation and solve for y
anonymous
  • anonymous
Sorry did the math wrong v.v
automaticloveletter
  • automaticloveletter
It's alright
TheSmartOne
  • TheSmartOne
y = 2(-3) − 1 solve for y
anonymous
  • anonymous
y=-7
automaticloveletter
  • automaticloveletter
and then -7 thanks i got it :)
TheSmartOne
  • TheSmartOne
(:
anonymous
  • anonymous
To solve a system of equations by substitution you need to follow these three steps: 1. Solve one equation for one variable. 2. Substitute what that variable is equal to in the other equation and solve for the other variable. Now one variable is known. 3. Substitute the known variable into one of the two original equations, and solve for the other variable. Let's do it here, one step at a time: Step 1. Since the first equation is already solved for y, step 1 is done, y = (1/2)x - 6 Step 2. Substitute what y is equal to in the other equation: 2x + 6y = 19, but y = (1/2)x - 6, so 2x + 6( (1/2)x - 6) = 19 Distribute the 6 on the left side: 2x + 3x - 36 = 19 Combine 2x and 3x: 5x - 36 = 19 Add 36 to both sides: 5x = 55 Divide both sides by 5: x = 11 Step 3. Substitute x in one of the two original equations: y = (1/2)x - 6 y = (1/2)11 - 6 y = 11/2 - 6 Use LCD of 2 to subtract fractions: y = 11/2 - 12/2 y = -1/2 hope this help

Looking for something else?

Not the answer you are looking for? Search for more explanations.